Cobalt-free NiMnAl precursor with composite structure, preparation method of cobalt-free NiMnAl precursor, positive electrode material, lithium ion battery and electric equipment
By adopting a cobalt-free NiMnAl precursor with a composite structure, the monoclinic β-MOOH phase and hexagonal α phase are composed of to avoid the occurrence of trimanganese tetraoxide heterophase, the problem of degradation of the performance of manganese-based positive electrode materials in the prior art is solved, and the problem of degradation of the performance of manganese-based positive electrode materials in the prior art is realized. The preparation of high-performance and low-cost lithium-rich manganese-based positive electrode materials is achieved.
Patent Information
- Application Number
- CN202411525302.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-30
AI Technical Summary
In the prior art, the composite structure of manganese hydroxyl oxide has high humidity and oxygen sensitivity, and is prone to produce a trimanganese tetraoxide heterophase, resulting in a decrease in the capacity and performance of the manganese-based positive electrode material.
The cobalt-free NiMnAl precursor with a composite structure consists of monoclinic β-MOOH phase and hexagonal α phase. Through co-precipitation reaction and drying treatment, the production of trimanganese tetraoxide heterophase is avoided, forming a tightly packed nanoparticles of flakes. Secondary particles ensure uniformity of morphology and element distribution.
It realizes the preparation of low-cost and high-performance lithium-rich manganese-based positive electrode materials, improves the capacity and performance of the material, avoids the occurrence of miscellaneous phases of trimanganese tetroxide, and ensures uniform particle size distribution and good spherical shape.
Smart Images

Figure CN119284988A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of new energy technology, and in particular to a cobalt-free NiMnAl precursor with a composite structure and a preparation method thereof, a positive electrode material, a lithium-ion battery and an electrical device. Background Art
[0002] At present, there is no related report on using composite structure oxyhydroxide as raw material to prepare manganese-based positive electrode materials. The main reason is that in the layered oxyhydroxide manganese in the composite structure, manganese is +3 valence, sensitive to humidity and oxygen, highly active and unstable, and easily produces manganese tetraoxide to form a mixed phase, causing uneven morphology and element distribution, resulting in reduced capacity and performance of the positive electrode material. In view of this, it is indeed necessary to provide a technical solution to the above problems. Summary of the invention
[0003] The purpose of the present application is to provide a composite cobalt-free NiMnAl precursor and its preparation method, positive electrode material, lithium-ion battery and electrical equipment, aiming to solve the problem in the prior art that the composite structure of hydroxyl oxide is prone to produce manganese tetraoxide impurities, resulting in reduced capacity and performance of the positive electrode material.
[0004] To achieve the above objectives, the present application provides a cobalt-free NiMnAl precursor with a composite structure, characterized in that the cobalt-free NiMnAl precursor with a composite structure is composed of a monoclinic β-MOOH phase and a hexagonal α phase.
[0005] In some embodiments, the cobalt-free NiMnAl precursor of the composite structure includes secondary particles formed by stacking a plurality of flaky nano primary particles, and the secondary particles satisfy at least one of the following conditions:
[0006] A. The particle size D50 of the secondary particles is 3 to 5 μm;
[0007] B. The tap density of the secondary particles is 1.0 to 1.55 g / cm 3 .
[0008] In some embodiments, at least one of the following conditions is met:
[0009] A. The monoclinic β-MOOH phase satisfies: α=90°, β=108°~109°, γ=90°;
[0010] B. The hexagonal α phase satisfies: α=90°, β=90°, γ=120°;
[0011] C. The cobalt-free NiMnAl precursor of the composite structure has no tetragonal phase (Ni xMn 1-x )3O4;
[0012] D. Na of the cobalt-free NiMnAl precursor of the composite structure is less than 120 ppm;
[0013] E. The S of the cobalt-free NiMnAl precursor of the composite structure is less than 1800 ppm.
[0014] In some embodiments, the chemical formula of the monoclinic β-MOOH phase of the cobalt-free NiMnAl precursor of the composite structure is Ni x-τ M τ Mn 1-x OOH, the chemical formula of the hexagonal α phase is (Ni x-τ M τ Mn 1-x ) 1-t Al t (OH)2(CO3) t / 2 The content of the hexagonal α phase is m, the content of the monoclinic β-MOOH phase is 1-m, and the overall chemical formula of the cobalt-free NiMnAl precursor of the composite structure is m(Ni x-τ M τ Mn 1-x ) 1-t Al t (OH)2(CO3) t / 2 ·(1-m)Ni x-τ M τ Mn 1-x OOH, wherein M is one or more of Ca, Mg, Fe, Cu, Zn, and Cd, τ<0.01, 0.25<x<0.50, 0.005<mt<0.01, 0.035<m<0.06, 1 / 6≤t≤1 / 4.
[0015] The present application also provides a method for preparing the above-mentioned cobalt-free NiMnAl precursor of the composite structure, comprising:
[0016] Passing a mixed metal salt solution, a precipitant, a complexing agent and an oxidant into the bottom liquid of a reactor to perform a coprecipitation reaction to obtain a slurry, and separating the slurry to obtain a solid precipitate;
[0017] The solid phase precipitate and the aging solution are mixed to carry out aging reaction and washing to obtain an aging product;
[0018] The aged product is sequentially subjected to a first drying process to a moisture content of less than 5% and a second drying process to a moisture content of less than 1%, wherein the temperature of the first drying process is lower than the temperature of the second drying process, to obtain the cobalt-free NiMnAl precursor of the composite structure.
[0019] In some embodiments, at least one of the following conditions is met:
[0020] A. the molar concentration of the oxidant in the coprecipitation reaction system is less than 5% of the total metal ion concentration in the mixed metal salt solution;
[0021] B. the temperature of the coprecipitation reaction is 45-55°C;
[0022] C. the pH of the coprecipitation reaction is 9.9 to 11.5;
[0023] D. The stirring speed of the coprecipitation reaction is 400-500 rpm;
[0024] E. The oxidant includes one or more of sodium hypochlorite, sodium persulfate, hydrogen peroxide, compressed air or a nitrogen / air mixture;
[0025] F. The molar concentration of the complexing agent in the coprecipitation reaction system is less than 1% of the total metal ion concentration in the mixed metal salt solution;
[0026] G. The color of the slurry is quantitatively measured by a Lab colorimeter, with an L value of 40 to 50, an a value of 0 to 4, and a b value of 20 to 25;
[0027] H. The flow rate of the mixed metal salt solution is 80 to 360 mL / min.
[0028] In some embodiments, at least one of the following conditions is met:
[0029] A. The mixed metal salt solution is a soluble salt solution of nickel, manganese and aluminum metals, and the soluble salt includes one or more of soluble sulfates, nitrates, acetates or chlorides;
[0030] B. The total metal ion concentration in the mixed metal salt solution is 0.5 to 4 mol / L;
[0031] C. the precipitating agent comprises one or more of sodium hydroxide, sodium carbonate, potassium hydroxide and lithium hydroxide;
[0032] D. the concentration of the precipitant is 1 to 10 mol / L;
[0033] E. The complexing agent includes one or more of ammonia water, ammonium sulfate, ammonium carbonate, and ammonium bicarbonate;
[0034] F. The concentration of the complexing agent is 0.1 to 5 mol / L;
[0035] G. the aging solution comprises one or more of sodium hydroxide, sodium carbonate, and sodium bicarbonate;
[0036] H. The temperature of the first drying is not higher than 60°C;
[0037] I. The temperature of the second drying is not higher than 110°C.
[0038] The present application also provides a positive electrode material, which is prepared from the above-mentioned cobalt-free NiMnAl precursor with a composite structure.
[0039] The present application also provides a lithium-ion battery, comprising the above-mentioned positive electrode material.
[0040] The present application also provides an electrical device, comprising the above-mentioned lithium-ion battery.
[0041] Compared with the prior art, the beneficial effects of this application include:
[0042] The cobalt-free NiMnAl precursor of the composite structure provided in the present application is composed of a monoclinic β-MOOH phase and a hexagonal α phase. The cobalt-free NiMnAl precursor of the composite structure does not produce a manganese tetraoxide impurity phase, and thus secondary particles composed of closely packed flaky nanoparticles with uniform morphology and element distribution can be obtained. The secondary particles have uniform particle size distribution, good sphericity, and high specific gravity, and can be used to prepare low-cost, high-performance lithium-rich manganese-based positive electrode materials.
[0043] The method for preparing a cobalt-free NiMnAl precursor with a composite structure provided in the present application comprises adding an oxidant during the coprecipitation reaction, and sequentially performing low-temperature pre-drying and high-temperature drying on the coprecipitation product, with the aim of stabilizing the layered manganese oxide hydroxyl without introducing a manganese tetraoxide impurity phase, and simultaneously introducing a small amount of α phase through trivalent aluminum to form a microscopic composite structure, thereby preparing a cobalt-free NiMnAl precursor composed of a monoclinic β-MOOH phase and a hexagonal α phase. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0045] Figure 1 This is a SEM image of the cobalt-free NiMnAl precursor of the composite structure prepared in Example 2;
[0046] Figure 2 The XRD pattern of the cobalt-free NiMnAl precursor of the composite structure prepared in Example 2;
[0047] Figure 3 This is a SEM image of the cobalt-free NiMnAl precursor of the composite structure prepared in Example 5;
[0048] Figure 4 This is the XRD pattern of the cobalt-free NiMnAl precursor of the composite structure prepared in Example 5;
[0049] Figure 5 This is a SEM image of the cobalt-free nickel-manganese precursor prepared in Comparative Example 1;
[0050] Figure 6 XRD pattern of the cobalt-free nickel-manganese precursor prepared in Comparative Example 1
[0051] Figure 7 This is a SEM image of the cobalt-free nickel-manganese precursor prepared in Comparative Example 2;
[0052] Figure 8 This is the XRD pattern of the cobalt-free nickel-manganese precursor prepared in Comparative Example 2. DETAILED DESCRIPTION
[0053] As used herein:
[0054] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0055] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0056] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0057] In these examples, parts and percentages are by mass unless otherwise indicated.
[0058] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0059] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0060] The unit cell is the smallest repeating unit in the crystal structure, which can build the entire crystal structure by repeating itself. The side length and the angle between the sides of the unit cell are important parameters that describe the geometric characteristics of the unit cell, usually expressed by the lattice constant. The lattice constant includes the three side lengths (a, b, c) and the angles between the three sides (α, β, γ).
[0061] In crystallography, the lengths and angles of the unit cell are very important in determining the symmetry and space group of the crystal. For example, the unit cell parameters of the cubic system are characterized by a=b=c, and α=β=γ=90°. This means that all sides of the cubic system unit cell are equal in length, and all angles between the sides are right angles.
[0062] For other crystal systems, the side lengths and angles of the unit cell have different relationships. For example, the unit cell parameters of the tetragonal system are a=b≠c, and α=β=γ=90°; the unit cell parameters of the hexagonal system are a=b≠c, α=β=90°, γ=120°; and the unit cell parameters of the triclinic system are a≠b≠c, and α≠β≠γ≠90°.
[0063] The size and shape of the unit cell are determined by these lattice parameters, which are the basic descriptors of the crystal structure. In practical material science research, the lattice constant is the basic structural parameter of crystalline materials and is directly related to the binding energy between atoms. Changes in the lattice constant can reflect changes in the composition, stress state, etc. inside the crystal. Usually, the SI unit of the lattice constant is meter, but in practical applications, the lattice constant is usually in a few angstroms. of the order of magnitude, i.e. a few tenths of a nanometer.
[0064] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0065] Example 1
[0066] This embodiment first provides a cobalt-free NiMnAl precursor, and the preparation method thereof comprises the following steps:
[0067] ① Preparation of feed solution: Dissolve nickel sulfate, ferrous sulfate, manganese sulfate and aluminum sulfate in deionized water according to the stoichiometric molar ratio of Ni:Fe:Mn:Al=0.2772:0.001:0.7128:0.009 to prepare a mixed metal ion solution with a total metal ion concentration of 2 mol / L. Add water to industrial-grade liquid caustic soda to prepare a 10 mol / L precipitant solution. Dissolve concentrated ammonia in water to prepare a 6 mol / L complexing agent solution.
[0068] ② Coprecipitation reaction: add 80L of water and appropriate amounts of ammonia water and alkali solution into a 100L reactor, adjust the ammonia concentration to 0.015mol / L, the pH value to 11.00-11.20, the reaction temperature to 45°C, and the stirring speed to 500r / min; and pump the mixed metal ion salt solution, alkali solution and ammonia solution into the reactor for coprecipitation reaction, and at the same time, introduce a mixed gas of nitrogen and air at 90L / h, the nitrogen / oxygen ratio is 5, the molar concentration of oxygen in the system is 2.3% of the total metal ion concentration in the mixed metal salt solution, the flow rate of the mixed metal salt solution is 240mL / min, and the alkali solution and ammonia solution are pumped in to adjust the pH value of the system to 10.30 and the ammonia concentration to 0.015mol / L, so as to stably control the particles to be maintained in the range of 3.0-5.0 microns, and the residence time of the slurry in the reactor is controlled to be 14-15 hours. During the reaction, due to the oxidizing effect of the oxidant, part of the divalent manganese in the precipitation material was oxidized to trivalent manganese, and the color of the material was light brown. The Lab values of an appropriate amount of slurry measured by a colorimeter were 48.6, 3.9, and 21.3, respectively. The precipitation reaction slurry was discharged into the aging tank through the overflow port.
[0069] ③ After the material flowing into the aging tank is separated, 100L of dilute alkali for aging is used for 100kg of material, and it is aged for 30 minutes in a 5% sodium hydroxide solution at 70℃ and washed until the supernatant of the slurry is neutral, and then separated and dewatered.
[0070] ④ The dehydrated material was pre-dried at 60°C to a moisture content of less than 5%, and then dried at 110°C to a moisture content of less than 1% to obtain the cobalt-free NiMnAl precursor of the composite structure of Example 1, whose chemical formula is 0.05 (Ni 0.28 Mn 0.72 ) 0.8 (Al 0.9 Fe 0.1 ) 0.2 (OH)2(CO3) 0.1 0.95Ni 0.28 Mn 0.72 OOH.
[0071] This embodiment also provides a positive electrode material, and the preparation method thereof is as follows: the precursor material obtained in step ④ and lithium hydroxide are mixed in a molar ratio of 1:1.12, and sintered at 950° C. in an oxygen atmosphere for 5 hours to obtain a positive electrode material.
[0072] This embodiment also provides a battery, wherein the positive electrode material obtained in this embodiment is assembled into a button-type battery according to a conventional method in the art.
[0073] Example 2
[0074] This embodiment first provides a cobalt-free NiMnAl precursor, and the preparation method thereof comprises the following steps:
[0075] ① Preparation of feed solution: Dissolve nickel sulfate, manganese sulfate and aluminum sulfate in deionized water at a stoichiometric molar ratio of Ni:Mn:Al=0.2775:0.7135:0.009 to prepare a mixed metal ion solution with a total metal ion concentration of 2 mol / L. Add water to industrial-grade liquid caustic soda to prepare a 10 mol / L precipitant solution. Dissolve concentrated ammonia in water to prepare a 6 mol / L complexing agent solution.
[0076] ② Coprecipitation reaction: add 80L of water and appropriate amounts of ammonia water and alkali solution into a 100L reactor, adjust the ammonia concentration to 0.015mol / L, the pH value to 11.00-11.20, the reaction temperature to 45°C, and the stirring speed to 500r / min; and pump the mixed metal ion salt solution, alkali solution and ammonia solution into the reactor for coprecipitation reaction, and introduce hydrogen peroxide at the same time. The molar concentration of hydrogen peroxide in the system is 3.8% of the total metal ion concentration in the mixed metal salt solution. The flow rate of the mixed metal salt solution is 240mL / min. The alkali solution and ammonia solution are pumped in to adjust the pH value of the system to 10.20 and the ammonia concentration to 0.015mol / L to stably control the particles to be maintained in the range of 3.0-5.0 microns. The residence time of the slurry in the reactor is controlled to be 14-15 hours. During the reaction, due to the oxidizing effect of the oxidant, part of the divalent manganese in the precipitation material was oxidized to trivalent manganese, and the color of the material was light brown. The Lab values of an appropriate amount of slurry measured by a colorimeter were 45.2, 2.6, and 22.9, respectively. The precipitation reaction slurry was discharged into the aging tank through the overflow port.
[0077] ③ After the material flowing into the aging tank is separated, 100L of dilute alkali for aging is used for 100kg of material, and it is aged for 30 minutes in a 5% sodium hydroxide solution at 70℃ and washed until the supernatant of the slurry is neutral, and then separated and dewatered.
[0078] ④ The dehydrated material was pre-dried at 60°C to a moisture content of less than 5%, and then dried at 110°C to a moisture content of less than 1% to obtain the cobalt-free NiMnAl precursor of the composite structure of Example 2, the chemical formula of which is 0.045 (Ni 0.28 Mn 0.72 ) 0.8 Al 0.2 (OH)2(CO3) 0.1 0.955Ni 0.28 Mn 0.72 OOH, its SEM picture is as follows Figure 1 As shown in FIG. 1 , it can be seen that the morphology of the precursor is a secondary particle formed by the accumulation of multiple thin-sheet nano primary particles. The nanosheets are small and uniform, with small pores between the sheets, and there are no irregular particles (impurities) on the surface of the secondary particles. The XRD pattern is shown in FIG. Figure 2 As shown, according to the XRD spectrum, the precursor is composed of a main phase β-MOOH and an auxiliary phase α, wherein 19°, 34°, and 38° correspond to the β-MOOH phase; and 11° and 23° correspond to the α phase.
[0079] This embodiment also provides a positive electrode material, and the preparation method thereof is as follows: the precursor material obtained in step ④ and lithium hydroxide are mixed in a molar ratio of 1:1.12, and sintered at 950° C. in an oxygen atmosphere for 5 hours to obtain a positive electrode material.
[0080] This embodiment also provides a battery, wherein the positive electrode material obtained in this embodiment is assembled into a button-type battery according to a conventional method in the art.
[0081] Example 3
[0082] This embodiment first provides a cobalt-free NiMnAl precursor, and the preparation method thereof comprises the following steps:
[0083] ① Preparation of feed solution: Dissolve nickel sulfate, manganese sulfate and aluminum sulfate in deionized water at a stoichiometric molar ratio of Ni:Mn:Al=0.2775:0.7135:0.009 to prepare a mixed metal ion solution with a total metal ion concentration of 2 mol / L. Add water to industrial-grade liquid caustic soda to prepare a 10 mol / L precipitant solution. Dissolve concentrated ammonia in water to prepare a 6 mol / L complexing agent solution.
[0084] ② Coprecipitation reaction: add 80L of water and appropriate amounts of ammonia water and alkali solution into a 100L reactor, adjust the ammonia concentration to 0.015mol / L, the pH value to 11.00-11.20, the reaction temperature to 45°C, and the stirring speed to 500r / min; and pump the mixed metal ion salt solution, alkali solution and ammonia solution into the reactor for coprecipitation reaction, and at the same time introduce an aqueous solution of sodium persulfate, the molar concentration of sodium persulfate in the system is 4.5% of the total metal ion concentration in the mixed metal salt solution, the flow rate of the mixed metal salt solution is 240mL / min, pump the alkali solution and ammonia solution into the reactor to adjust the pH value of the system to 10.10 and the ammonia concentration to 0.015mol / L to stably control the particles to be maintained in the range of 3.0-5.0 microns, and the residence time of the slurry in the reactor is controlled to be 14-15 hours. During the reaction, due to the oxidizing effect of the oxidant, part of the divalent manganese in the precipitation material was oxidized to trivalent manganese, and the color of the material was light brown. The Lab values of an appropriate amount of slurry measured by a colorimeter were 41.8, 0.6, and 24.4, respectively. The precipitation reaction slurry was discharged into the aging tank through the overflow port.
[0085] ③ After the material flowing into the aging tank is separated, 100L of dilute alkali for aging is used for 100kg of material, and it is aged for 30 minutes in a 5% sodium hydroxide solution at 70℃ and washed until the supernatant of the slurry is neutral, and then separated and dewatered.
[0086] ④ The dehydrated material was pre-dried at 60°C to a moisture content of less than 5%, and then dried at 110°C to a moisture content of less than 1% to obtain the cobalt-free NiMnAl precursor of the composite structure of Example 3, whose chemical formula is 0.045 (Ni 0.28 Mn 0.72 ) 0.8 Al 0.2 (OH)2(CO3) 0.1 0.955Ni0.28 Mn 0.72 OOH.
[0087] This embodiment also provides a positive electrode material, and the preparation method thereof is as follows: the precursor material obtained in step ④ and lithium hydroxide are mixed in a molar ratio of 1:1.12, and sintered at 950° C. in an oxygen atmosphere for 5 hours to obtain a positive electrode material.
[0088] This embodiment also provides a battery, wherein the positive electrode material obtained in this embodiment is assembled into a button-type battery according to a conventional method in the art.
[0089] Example 4
[0090] This embodiment first provides a cobalt-free NiMnAl precursor, and the preparation method thereof comprises the following steps:
[0091] ① Preparation of feed solution: Dissolve nickel sulfate, manganese sulfate and aluminum nitrate in deionized water at a stoichiometric molar ratio of Ni:Mn:Al=:0.331:0.661:0.008 to prepare a mixed metal ion solution with a total metal ion concentration of 2 mol / L. Add water to industrial-grade liquid caustic soda to prepare a 10 mol / L precipitant solution. Dissolve concentrated ammonia in water to prepare a 6 mol / L complexing agent solution.
[0092] ② Coprecipitation reaction: add 80L of water and appropriate amounts of ammonia water and alkali solution into a 100L reactor, adjust the ammonia concentration to 0.018mol / L, the pH value to 11.00-11.20, the reaction temperature to 50°C, and the stirring speed to 450r / min; and pump the mixed metal ion salt solution, alkali solution and ammonia solution into the reactor for coprecipitation reaction, and at the same time, introduce a mixed gas of nitrogen and air at 60L / h, the nitrogen / oxygen ratio is 5, the molar concentration of oxygen in the system is 2.5% of the total metal ion concentration in the mixed metal salt solution, the flow rate of the mixed metal salt solution is 160mL / min, pump in alkali solution and ammonia solution to adjust the pH value of the system to 10.35 and the ammonia concentration to 0.018mol / L to stably control the particles to be maintained in the range of 3.0-5.0 microns, and the residence time of the slurry in the reactor is controlled to be 14-15 hours. During the reaction, due to the oxidizing effect of the oxidant, part of the divalent manganese in the precipitation material was oxidized to trivalent manganese, and the color of the material was light brown. The Lab values of an appropriate amount of slurry measured by a colorimeter were 47.2, 3.4, and 20.5, respectively. The precipitation reaction slurry was discharged into the aging tank through the overflow port.
[0093] ③ After the material flowing into the aging tank is separated, 100L of dilute alkali for aging is used for 100kg of material, and it is aged for 30 minutes in a 5% sodium hydroxide solution at 70℃ and washed until the supernatant of the slurry is neutral, and then separated and dewatered.
[0094] ④ The dehydrated material was pre-dried at 60°C to a moisture content of less than 5%, and then dried at 110°C to a moisture content of less than 1% to obtain the cobalt-free NiMnAl precursor of the composite structure of Example 4, whose chemical formula is 0.04 (Ni 0.333 Mn 0.667 ) 0.8 Al 0.2 (OH)2(CO3) 0.1 0.96Ni 0.333 Mn 0.667 OOH.
[0095] This embodiment also provides a positive electrode material, and the preparation method thereof is as follows: the precursor material obtained in step ④ and lithium hydroxide are mixed in a molar ratio of 1:1.12, and sintered at 950° C. in an oxygen atmosphere for 5 hours to obtain a positive electrode material.
[0096] This embodiment also provides a battery, wherein the positive electrode material obtained in this embodiment is assembled into a button-type battery according to a conventional method in the art.
[0097] Example 5
[0098] This embodiment first provides a cobalt-free NiMnAl precursor, and the preparation method thereof comprises the following steps:
[0099] ① Preparation of feed solution: Dissolve nickel sulfate, manganese sulfate and aluminum nitrate in deionized water at a stoichiometric molar ratio of Ni:Mn:Al=0.331:0.661:0.008 to prepare a mixed metal ion solution with a total metal ion concentration of 2 mol / L. Add water to industrial-grade liquid caustic soda to prepare a 10 mol / L precipitant solution. Dissolve concentrated ammonia in water to prepare a 6 mol / L complexing agent solution.
[0100] ② Coprecipitation reaction: add 80L of water and appropriate amounts of ammonia water and alkali solution into a 100L reactor, adjust the ammonia concentration to 0.018mol / L, the pH value to 11.00-11.20, the reaction temperature to 50°C, and the stirring speed to 450r / min; and pump the mixed metal ion salt solution, alkali solution and ammonia solution into the reactor for coprecipitation reaction, and introduce hydrogen peroxide at the same time, the molar concentration of hydrogen peroxide in the system is 3.0% of the total metal ion concentration in the mixed metal salt solution, the flow rate of the mixed metal salt solution is 160mL / min, pump the alkali solution and ammonia solution to adjust the pH value of the system to 10.25 and the ammonia concentration to 0.018mol / L to stably control the particles to be maintained in the range of 3.0-5.0 microns, and the residence time of the slurry in the reactor is controlled to be 14-15 hours. During the reaction, due to the oxidizing effect of the oxidant, part of the divalent manganese in the precipitation material was oxidized to trivalent manganese, and the color of the material was light brown. The Lab values of an appropriate amount of slurry measured by a colorimeter were 44.6, 2.4, and 23.2, respectively. The precipitation reaction slurry was discharged into the aging tank through the overflow port.
[0101] ③ After the material flowing into the aging tank is separated, 100L of dilute alkali for aging is used for 100kg of material, and it is aged for 30 minutes in a 5% sodium hydroxide solution at 70℃ and washed until the supernatant of the slurry is neutral, and then separated and dewatered.
[0102] ④ The dehydrated material was pre-dried at 60°C to a moisture content of less than 5%, and then dried at 110°C to a moisture content of less than 1% to obtain the cobalt-free NiMnAl precursor of the composite structure of Example 5, the chemical formula of which is 0.04 (Ni 0.333 Mn 0.667 ) 0.8 Al 0.2 (OH)2(CO3) 0.1 0.96Ni 0.333 Mn 0.667 OOH, its SEM picture is as follows Figure 3 As shown in FIG. 1 , it can be seen that the morphology of the precursor is a secondary particle formed by the accumulation of multiple thin-sheet nano primary particles. The nanosheets are small and uniform, with small pores between the sheets, and there are no irregular particles (impurities) on the surface of the secondary particles. The XRD pattern is shown in FIG. Figure 4 As shown, according to the XRD spectrum, the precursor is composed of a main phase β-MOOH and an auxiliary phase α, wherein 19°, 34°, and 38° correspond to the β-MOOH phase; and 11° and 23° correspond to the α phase.
[0103] This embodiment also provides a positive electrode material, and the preparation method thereof is as follows: the precursor material obtained in step ④ and lithium hydroxide are mixed in a molar ratio of 1:1.12, and sintered at 950° C. in an oxygen atmosphere for 5 hours to obtain a positive electrode material.
[0104] This embodiment also provides a battery, wherein the positive electrode material obtained in this embodiment is assembled into a button-type battery according to a conventional method in the art.
[0105] Example 6
[0106] This embodiment first provides a cobalt-free NiMnAl precursor, and the preparation method thereof comprises the following steps:
[0107] ① Preparation of feed solution: Dissolve nickel sulfate, manganese sulfate and aluminum nitrate in deionized water at a stoichiometric molar ratio of Ni:Mn:Al=0.331:0.661:0.008 to prepare a mixed metal ion solution with a total metal ion concentration of 2 mol / L. Add water to industrial-grade liquid caustic soda to prepare a 10 mol / L precipitant solution. Dissolve concentrated ammonia in water to prepare a 6 mol / L complexing agent solution.
[0108] ② Coprecipitation reaction: add 80L of water and appropriate amounts of ammonia water and alkali solution into a 100L reactor, adjust the ammonia concentration to 0.018mol / L, the pH value to 11.00-11.20, the reaction temperature to 50°C, and the stirring speed to 450r / min; and pump the mixed metal ion salt solution, alkali solution and ammonia solution into the reactor for coprecipitation reaction, and at the same time introduce an aqueous solution of sodium persulfate, the molar concentration of sodium persulfate in the system is 4.2% of the total metal ion concentration in the mixed metal salt solution, the flow rate of the mixed metal salt solution is 160mL / min, pump in alkali solution and ammonia solution to adjust the pH value of the system to 10.15 and the ammonia concentration to 0.018mol / L to stably control the particles to be maintained in the range of 3.0-5.0 microns, and the residence time of the slurry in the reactor is controlled to be 14-15 hours. During the reaction, due to the oxidizing effect of the oxidant, part of the divalent manganese in the precipitation material was oxidized to trivalent manganese, and the color of the material was light brown. The Lab values of an appropriate amount of slurry measured by a colorimeter were 40.9, 0.9, and 25.0, respectively. The precipitation reaction slurry was discharged into the aging tank through the overflow port.
[0109] ③ After the material flowing into the aging tank is separated, 100L of dilute alkali for aging is used for 100kg of material, and it is aged for 30 minutes in a 5% sodium hydroxide solution at 70℃ and washed until the supernatant of the slurry is neutral, and then separated and dewatered.
[0110] ④ The dehydrated material was pre-dried at 60°C to a moisture content of less than 5%, and then dried at 110°C to a moisture content of less than 1% to obtain the cobalt-free NiMnAl precursor of the composite structure of Example 6, whose chemical formula is 0.04 (Ni 0.333 Mn 0.667 ) 0.8 Al 0.2 (OH)2(CO3) 0.1 0.96Ni 0.333Mn 0.667 OOH.
[0111] This embodiment also provides a positive electrode material, and the preparation method thereof is as follows: the precursor material obtained in step ④ and lithium hydroxide are mixed in a molar ratio of 1:1.12, and sintered at 950° C. in an oxygen atmosphere for 5 hours to obtain a positive electrode material.
[0112] This embodiment also provides a battery, wherein the positive electrode material obtained in this embodiment is assembled into a button-type battery according to a conventional method in the art.
[0113] Example 7
[0114] This embodiment first provides a cobalt-free NiMnAl precursor, and the preparation method thereof comprises the following steps:
[0115] ① Preparation of feed solution: Dissolve nickel sulfate, magnesium sulfate, manganese sulfate and aluminum chloride in deionized water according to the stoichiometric molar ratio of Ni:Mg:Mn:Al=0.3465:0.004:0.6435:0.006 to prepare a mixed metal ion solution with a total metal ion concentration of 2 mol / L. Add water to industrial-grade liquid caustic soda to prepare a 10 mol / L precipitant solution. Dissolve concentrated ammonia in water to prepare a 6 mol / L complexing agent solution.
[0116] ② Coprecipitation reaction: add 80L of water and appropriate amounts of ammonia water and alkali solution into a 100L reactor, adjust the ammonia concentration to 0.020mol / L, the pH value to 11.00-11.20, the reaction temperature to 52°C, and the stirring speed to 420r / min; and pump the mixed metal ion salt solution, alkali solution and ammonia solution into the reactor for coprecipitation reaction, and at the same time, introduce a mixed gas of nitrogen and air at 45L / h, the nitrogen / oxygen ratio is 5, the molar concentration of oxygen in the system is 2.3% of the total metal ion concentration in the mixed metal salt solution, the flow rate of the mixed metal salt solution is 120mL / min, pump in alkali solution and ammonia solution to adjust the pH value of the system to 10.45 and the ammonia concentration to 0.020mol / L to stably control the particles to be maintained in the range of 3.0-5.0 microns, and the residence time of the slurry in the reactor is controlled to be 14-15 hours. During the reaction, due to the oxidizing effect of the oxidant, part of the divalent manganese in the precipitation material is oxidized to trivalent manganese, the material color is light brown, and the precipitation reaction slurry is discharged into the aging tank through the overflow port.
[0117] ③ After the material flowing into the aging tank is separated, 100L of dilute alkali for aging is used for 100kg of material, and it is aged for 30 minutes in a 5% sodium hydroxide solution at 70℃ and washed until the supernatant of the slurry is neutral, and then separated and dewatered.
[0118] ④ The dehydrated material was pre-dried at 60°C to a moisture content of less than 5%, and then dried at 110°C to a moisture content of less than 1% to obtain the cobalt-free NiMnAl precursor of the composite structure of Example 7, whose chemical formula is 0.036 (Ni 0.348 Mg 0.004 Mn 0.648 ) 5 / 6 Al 1 / 6 (OH)2(CO3) 1 / 12 0.964Ni 0.348 Mg 0.004 Mn 0.648 OOH.
[0119] This embodiment also provides a positive electrode material, and the preparation method thereof is as follows: the precursor material obtained in step ④ and lithium hydroxide are mixed in a molar ratio of 1:1.12, and sintered at 950° C. in an oxygen atmosphere for 5 hours to obtain a positive electrode material.
[0120] This embodiment also provides a battery, wherein the positive electrode material obtained in this embodiment is assembled into a button-type battery according to a conventional method in the art.
[0121] Example 8
[0122] This embodiment first provides a cobalt-free NiMnAl precursor, and the preparation method thereof comprises the following steps:
[0123] ① Preparation of feed solution: Nickel sulfate, manganese sulfate and aluminum chloride are dissolved in deionized water according to the stoichiometric molar ratio of Ni:Mn:Al=0.3479:0.6461:0.006 to prepare a mixed metal ion solution with a total metal ion concentration of 2 mol / L. Add water to industrial-grade liquid caustic soda to prepare a 10 mol / L precipitant solution. Dissolve concentrated ammonia in water to prepare a 6 mol / L complexing agent solution.
[0124] ② Coprecipitation reaction: add 80L water and appropriate amount of ammonia water and alkali solution into a 100L reactor, adjust the ammonia concentration to 0.020mol / L, pH value to 11.00-11.20, reaction temperature to 52°C, stirring speed to 420r / min; and pump the mixed metal ion salt solution, alkali solution and ammonia solution into the reactor for coprecipitation reaction, and introduce hydrogen peroxide at the same time, the molar concentration of hydrogen peroxide in the system is 3.4% of the total metal ion concentration in the mixed metal salt solution, the mixed metal salt solution flow rate is 120mL / min, pump the alkali solution and ammonia solution into the system to adjust the pH value to 10.35 and the ammonia concentration to 0.020mol / L to stably control the particles to maintain within the range of 3.0-5.0 microns, and the residence time of the slurry in the reactor is controlled to be 14-15 hours. During the reaction, due to the oxidation of the oxidant, the divalent manganese in the precipitated material is partially oxidized to trivalent manganese, the material color is light brown, and the precipitation reaction slurry is discharged to the aging tank through the overflow port.
[0125] ③ After the material flowing into the aging tank is separated, 100L of dilute alkali for aging is used for 100kg of material, and it is aged for 30 minutes in a 5% sodium hydroxide solution at 70℃ and washed until the supernatant of the slurry is neutral, and then separated and dewatered.
[0126] ④ The dehydrated material was pre-dried at 60°C to a moisture content of less than 5%, and then dried at 110°C to a moisture content of less than 1% to obtain the cobalt-free NiMnAl precursor of the composite structure of Example 8, the chemical formula of which is 0.036 (Ni 0.35 Mn 0.65 ) 5 / 6Al 1 / 6 (OH)2(CO3) 1 / 12 0.964Ni 0.35 Mn 0.65 OOH.
[0127] This embodiment also provides a positive electrode material, and the preparation method thereof is as follows: the precursor material obtained in step ④ and lithium hydroxide are mixed in a molar ratio of 1:1.12, and sintered at 950° C. in an oxygen atmosphere for 5 hours to obtain a positive electrode material.
[0128] This embodiment also provides a battery, wherein the positive electrode material obtained in this embodiment is assembled into a button-type battery according to a conventional method in the art.
[0129] Example 9
[0130] This embodiment first provides a cobalt-free NiMnAl precursor, and the preparation method thereof comprises the following steps:
[0131] ① Preparation of feed solution: Nickel sulfate, manganese sulfate and aluminum chloride are dissolved in deionized water according to the stoichiometric molar ratio of Ni:Mn:Al=0.3479:0.6461:0.006 to prepare a mixed metal ion solution with a total metal ion concentration of 2 mol / L. Add water to industrial-grade liquid caustic soda to prepare a 10 mol / L precipitant solution. Dissolve concentrated ammonia in water to prepare a 6 mol / L complexing agent solution.
[0132] ② Coprecipitation reaction: add 80L of water and appropriate amounts of ammonia water and alkali solution into a 100L reactor, adjust the ammonia concentration to 0.020mol / L, the pH value to 11.00-11.20, the reaction temperature to 52°C, and the stirring speed to 420r / min; and pump the mixed metal ion salt solution, alkali solution and ammonia solution into the reactor for coprecipitation reaction, and at the same time introduce an aqueous solution of sodium persulfate, the molar concentration of sodium persulfate in the system is 4.3% of the total metal ion concentration in the mixed metal salt solution, the flow rate of the mixed metal salt solution is 120mL / min, pump in alkali solution and ammonia solution to adjust the pH value of the system to 10.25 and the ammonia concentration to 0.020mol / L to stably control the particles to be maintained in the range of 3.0-5.0 microns, and the residence time of the slurry in the reactor is controlled to be 14-15 hours. During the reaction, due to the oxidizing effect of the oxidant, part of the divalent manganese in the precipitation material is oxidized to trivalent manganese, the material color is light brown, and the precipitation reaction slurry is discharged into the aging tank through the overflow port.
[0133] ③ After the material flowing into the aging tank is separated, 100L of dilute alkali for aging is used for 100kg of material, and it is aged for 30 minutes in a 5% sodium hydroxide solution at 70℃ and washed until the supernatant of the slurry is neutral, and then separated and dewatered.
[0134] ④ The dehydrated material was pre-dried at 60°C to a moisture content of less than 5%, and then dried at 110°C to a moisture content of less than 1% to obtain the cobalt-free NiMnAl precursor of the composite structure of Example 9, whose chemical formula is 0.036 (Ni 0.35 Mn 0.65 ) 5 / 6Al 1 / 6 (OH)2(CO3) 1 / 12 0.964Ni 0.35 Mn 0.65 OOH.
[0135] This embodiment also provides a positive electrode material, and the preparation method thereof is as follows: the precursor material obtained in step ④ and lithium hydroxide are mixed in a molar ratio of 1:1.12, and sintered at 950° C. in an oxygen atmosphere for 5 hours to obtain a positive electrode material.
[0136] This embodiment also provides a battery, wherein the positive electrode material obtained in this embodiment is assembled into a button-type battery according to a conventional method in the art.
[0137] Comparative Example 1
[0138] This comparative example first provides a cobalt-free NiMn precursor, and its preparation method comprises the following steps:
[0139] ① Preparation of feed solution: Dissolve nickel sulfate and manganese sulfate in deionized water at a stoichiometric molar ratio of Ni:Mn=0.28:0.72 to prepare a mixed metal ion solution with a total metal ion concentration of 2 mol / L. Add water to industrial-grade liquid caustic soda to prepare a 10 mol / L precipitant solution. Dissolve concentrated ammonia in water to prepare a 6 mol / L complexing agent solution.
[0140] ② Coprecipitation reaction: add 80L water and appropriate amount of ammonia water and alkali solution into a 100L reactor, adjust the ammonia concentration to 0.015mol / L, pH value to 11.00-11.20, reaction temperature to 45℃, stirring speed to 500r / min; and pump the mixed metal ion salt solution, alkali solution and ammonia solution into the reactor for coprecipitation reaction, the mixed metal salt solution flow rate is 240mL / min, pump the alkali solution and ammonia solution into the reactor to adjust the pH value of the system to 10.20 and the ammonia concentration to 0.015mol / L to stably control the particles to be maintained within the range of 3.0-5.0 microns, and the residence time of the slurry in the reactor is controlled to be 14-15 hours. The precipitation reaction slurry is discharged to the aging tank through the overflow port.
[0141] ③ After the materials flowing into the aging tank are separated, they are aged in a 5% sodium hydroxide solution at 70°C for 30 minutes and washed until the supernatant of the slurry is neutral, and then separated and dewatered.
[0142] ④ The dehydrated material was dried at 110°C until the moisture content was below 1% to obtain the cobalt-free NiMn precursor of Comparative Example 1, the SEM image of which is shown in FIG. Figure 5 As shown in FIG. 1 , the morphology of the precursor is that multiple thin sheet-like nano primary particles are piled up into secondary particles. The nanosheets are coarse and uneven, with large pores between the sheets. Irregular particles (mixed phase) adhere to the surface of the secondary particles. The XRD pattern is shown in FIG. Figure 6 As shown, according to the XRD spectrum, the precursor is composed of the main phase β-MOOH and the auxiliary phase M3O4, among which 19°, 34°, and 38° correspond to the β-MOOH phase; 18°, 29°, 31°, 33°, 36°, and 45° correspond to the M3O4 phase.
[0143] This comparative example also provides a positive electrode material, and its preparation method is as follows: the precursor material obtained in step ④ and lithium hydroxide are mixed in a molar ratio of 1:1.12, and sintered at 950° C. in an oxygen atmosphere for 5 hours to obtain a positive electrode material.
[0144] This comparative example also provides a battery, and the positive electrode material obtained in this comparative example is assembled into a button-type battery according to a conventional method in the art.
[0145] Comparative Example 2
[0146] This comparative example first provides a cobalt-free NiMn precursor, and its preparation method comprises the following steps:
[0147] ① Preparation of feed solution: Dissolve nickel sulfate and manganese sulfate in deionized water at a stoichiometric molar ratio of Ni:Mn=0.333:0.667 to prepare a mixed metal ion solution with a total metal ion concentration of 2 mol / L. Add water to industrial-grade liquid caustic soda to prepare a 10 mol / L precipitant solution. Dissolve concentrated ammonia in water to prepare a 6 mol / L complexing agent solution.
[0148] ② Coprecipitation reaction: add 80L water and appropriate amount of ammonia water and alkali solution into a 100L reactor, adjust the ammonia concentration to 0.018mol / L, pH value to 11.00-11.20, reaction temperature to 50℃, stirring speed to 450r / min; and pump the mixed metal ion salt solution, alkali solution and ammonia solution into the reactor for coprecipitation reaction, the mixed metal salt solution flow rate is 160mL / min, pump the alkali solution and ammonia solution into the reactor to adjust the pH value of the system to 10.25 and the ammonia concentration to 0.018mol / L to stably control the particles to be maintained within the range of 3.0-5.0 microns, and the residence time of the slurry in the reactor is controlled to be 14-15 hours. The precipitation reaction slurry is discharged to the aging tank through the overflow port.
[0149] ③ After the materials flowing into the aging tank are separated, they are aged in a 5% sodium hydroxide solution at 70°C for 30 minutes and washed until the supernatant of the slurry is neutral, and then separated and dewatered.
[0150] ④ The dehydrated material was dried at 110°C until the moisture content was below 1% to obtain the cobalt-free NiMn precursor of Comparative Example 2, the SEM image of which is shown in FIG. Figure 7 As shown in FIG. 1 , the morphology of the precursor is that multiple thin sheet-like nano primary particles are piled up into secondary particles. The nanosheets are coarse and uneven, with large pores between the sheets. Irregular particles (mixed phase) adhere to the surface of the secondary particles. The XRD pattern is shown in FIG. Figure 8As shown, according to the XRD spectrum, the precursor is composed of the main phase β-MOOH and the auxiliary phase M3O4, among which 19°, 34°, and 38° correspond to the β-MOOH phase; 18°, 29°, 31°, 33°, 36°, and 45° correspond to the M3O4 phase.
[0151] This comparative example also provides a positive electrode material, and its preparation method is as follows: the precursor material obtained in step ④ and lithium hydroxide are mixed in a molar ratio of 1:1.12, and sintered at 950° C. in an oxygen atmosphere for 5 hours to obtain a positive electrode material.
[0152] This comparative example also provides a battery, and the positive electrode material obtained in this comparative example is assembled into a button-type battery according to a conventional method in the art.
[0153] Comparative Example 3
[0154] This comparative example first provides a cobalt-free NiMn precursor, and the preparation method thereof comprises the following steps:
[0155] ① Preparation of feed solution: Nickel sulfate and manganese sulfate are dissolved in deionized water at a stoichiometric molar ratio of Ni:Mn=0.35:0.65 to prepare a mixed metal ion solution with a total metal ion concentration of 2 mol / L. Add water to industrial-grade liquid alkali to prepare a 10 mol / L precipitant solution. Dissolve concentrated ammonia in water to prepare a 6 mol / L complexing agent solution.
[0156] ② Coprecipitation reaction: add 80L water and appropriate amount of ammonia water and alkali solution into a 100L reactor, adjust the ammonia concentration to 0.020mol / L, pH value to 11.00-11.20, reaction temperature to 52°C, stirring speed to 420r / min; and pump the mixed metal ion salt solution, alkali solution and ammonia solution into the reactor for coprecipitation reaction, the mixed metal salt solution flow rate is 120mL / min, pump the alkali solution and ammonia solution into the reactor to adjust the pH value of the system to 10.35 and the ammonia concentration to 0.020mol / L to stably control the particles to be maintained within the range of 3.0-5.0 microns, and the residence time of the slurry in the reactor is controlled to be 14-15 hours. The precipitation reaction slurry is discharged to the aging tank through the overflow port.
[0157] ③ After the materials flowing into the aging tank are separated, they are aged in a 5% sodium hydroxide solution at 70°C for 30 minutes and washed until the supernatant of the slurry is neutral, and then separated and dewatered.
[0158] ④ Dry the dehydrated material at 110° C. until the moisture content is below 1% to obtain the cobalt-free NiMn precursor of Comparative Example 3.
[0159] This comparative example also provides a positive electrode material, and its preparation method is as follows: the precursor material obtained in step ④ and lithium hydroxide are mixed in a molar ratio of 1:1.12, and sintered at 950° C. in an oxygen atmosphere for 5 hours to obtain a positive electrode material.
[0160] This comparative example also provides a battery, and the positive electrode material obtained in this comparative example is assembled into a button-type battery according to a conventional method in the art.
[0161] The D50, TD and the first discharge capacity of the corresponding batteries of the precursors of the composite structures prepared in Examples 1 to 9 and Comparative Examples 1 to 3 were detected and analyzed.
[0162] D50 test method: disperse an appropriate amount of powder material in water, use the ultrasonic disperser of Mastersizer 3000 to disperse for 30 seconds, and then perform particle size test according to the procedure.
[0163] TD test method: put 20g of powder material into the 50mL measuring cylinder that comes with the tap density meter and fix it. After sealing, start the motor to vibrate. Stop the vibration after 5 minutes, record the reading of the measuring cylinder, and get the tap density of the powder.
[0164] First discharge capacity: Charge at 0.1C constant current to 4.55V in the voltage range of 2.5V to 4.55V at 25℃, then charge at constant voltage to a cut-off current of 0.02C at 4.55V, leave for 5 minutes, discharge at 0.1C or 1 / 3C to 2.5V, leave for 5 minutes, and record the charge and discharge capacity after the first cycle.
[0165] The test results are shown in Table 1.
[0166] Table 1 Physicochemical parameters and electrochemical properties of the precursors of Examples 1 to 9 and Comparative Examples 1 to 3
[0167]
[0168] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0169] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A cobalt-free NiMnAl precursor of a composite structure, characterized in that: The cobalt-free NiMnAl precursor of the composite structure is composed of a monoclinic β-MOOH phase and a hexagonal α phase.
2. The cobalt-free NiMnAl precursor of the composite structure according to claim 1, characterized in that: The cobalt-free NiMnAl precursor of the composite structure includes secondary particles formed by stacking a plurality of flaky nano primary particles, and the secondary particles satisfy at least one of the following conditions: A. The particle size D50 of the secondary particles is 3 to 5 μm; B. The tap density of the secondary particles is 1.0 to 1.55 g / cm 3 .
3. The cobalt-free NiMnAl precursor of the composite structure according to claim 1, characterized in that: At least one of the following conditions is met: A. The monoclinic β-MOOH phase satisfies: α=90°, β=108°~109°, γ=90°; B. The hexagonal α phase satisfies: α=90°, β=90°, γ=120°; C. The cobalt-free NiMnAl precursor of the composite structure has no tetragonal phase (Ni x Mn 1-x )3O4; D. Na of the cobalt-free NiMnAl precursor of the composite structure is less than 120 ppm; E. The S of the cobalt-free NiMnAl precursor of the composite structure is less than 1800 ppm.
4. The cobalt-free NiMnAl precursor of the composite structure according to any one of claims 1 to 3, characterized in that: The chemical formula of the monoclinic β-MOOH phase of the cobalt-free NiMnAl precursor of the composite structure is Ni x-τ M τ Mn 1-x OOH, the chemical formula of the hexagonal α phase is (Ni x-τ M τ Mn 1-x ) 1-t Al t (OH)2(CO3) t / 2 The content of the hexagonal α phase accounts for m, and the content of the monoclinic β-MOOH phase accounts for 1-m. The overall chemical formula of the cobalt-free NiMnAl precursor of the composite structure is: m(Ni x-τ M τ Mn 1-x ) 1-t Al t (OH)2(CO3) t / 2 ·(1-m)Ni x-τ M τ Mn 1-x OOH, wherein M is one or more of Ca, Mg, Fe, Cu, Zn, and Cd, τ<0.01, 0.25<x<0.50, 0.005<mt<0.01, 0.035<m<0.06, 1 / 6≤t≤1 / 4.
5. A method for preparing a cobalt-free NiMnAl precursor of a composite structure according to any one of claims 1 to 4, characterized in that: include: Passing a mixed metal salt solution, a precipitant, a complexing agent and an oxidant into the bottom liquid of a reactor to perform a coprecipitation reaction to obtain a slurry, and separating the slurry to obtain a solid precipitate; The solid phase precipitate and the aging solution are mixed to carry out aging reaction and washing to obtain an aging product; The aged product is sequentially subjected to a first drying process to a moisture content of less than 5% and a second drying process to a moisture content of less than 1%, wherein the temperature of the first drying process is lower than the temperature of the second drying process, to obtain the cobalt-free NiMnAl precursor of the composite structure.
6. The method for preparing a cobalt-free NiMnAl precursor of a composite structure according to claim 5, characterized in that: At least one of the following conditions is met: A. the molar concentration of the oxidant in the coprecipitation reaction system is less than 5% of the total metal ion concentration in the mixed metal salt solution; B. the temperature of the coprecipitation reaction is 45-55°C; C. the pH of the coprecipitation reaction is 9.9 to 11.5; D. The stirring speed of the coprecipitation reaction is 400-500 rpm; E. The oxidant includes one or more of sodium hypochlorite, sodium persulfate, hydrogen peroxide, compressed air or a nitrogen / air mixture; F. The molar concentration of the complexing agent in the coprecipitation reaction system is less than 1% of the total metal ion concentration in the mixed metal salt solution; G. The color of the slurry is quantitatively measured by a Lab colorimeter, with an L value of 40 to 50, an a value of 0 to 4, and a b value of 20 to 25; H. The flow rate of the mixed metal salt solution is 80 to 360 mL / min.
7. The method for preparing a cobalt-free NiMnAl precursor of a composite structure according to claim 5 or 6, characterized in that: At least one of the following conditions is met: A. The mixed metal salt solution is a soluble salt solution of nickel, manganese and aluminum metals, and the soluble salt includes one or more of soluble sulfates, nitrates, acetates or chlorides; B. The total metal ion concentration in the mixed metal salt solution is 0.5 to 4 mol / L; C. the precipitating agent comprises one or more of sodium hydroxide, sodium carbonate, potassium hydroxide and lithium hydroxide; D. the concentration of the precipitant is 1 to 10 mol / L; E. The complexing agent includes one or more of ammonia water, ammonium sulfate, ammonium carbonate, and ammonium bicarbonate; F. The concentration of the complexing agent is 0.1 to 5 mol / L; G. the aging solution comprises one or more of sodium hydroxide, sodium carbonate, and sodium bicarbonate; H. The temperature of the first drying is not higher than 60°C; I. The temperature of the second drying is not higher than 110°C.
8. A positive electrode material, characterized in that The composite structure is prepared from the cobalt-free NiMnAl precursor according to any one of claims 1 to 4.
9. A lithium ion battery, characterized in that: Comprising the positive electrode material as claimed in claim 8.
10. An electrical device, characterized in that: Includes the lithium ion battery as claimed in claim 9.
Citation Information
Patent Citations
Preparation method of multivariate doping spherical alpha-Ni(OH)2 with nanometer secondary structure
CN101723473A
Cobalt-free lithium-rich ternary anode material NMA and preparation method thereof
CN109686970A
Nanometer alpha-nickel hydroxide and its prepn
CN1772629A
Core-shell composite phase-structured nickel hydroxide and its preparation method and application
CN1884101A
Method for producing nickel-manganese composite oxyhydroxide
JP2017178701A